The CNS-Penetrant Soluble Guanylate Cyclase Stimulator CY6463 Reveals its Therapeutic Potential in Neurodegenerative Diseases - Correia, Susana S.; Iyengar, Rajesh R.; Germano, Peter; Tang, Kim; Bernier, Sylvie G.; Schwartzkopf, Chad D.; Tobin, Jenny; Lee, Thomas W.-H.; Liu, Guang; Jacobson, Sarah; Carvalho, Andrew; Rennie, Glen R.; et al. (Frontiers in Pharmacology, 2021)
Effective treatments for neurodegenerative diseases remain elusive and are critically needed as the burden of these diseases increases across an aging global population. Nitric oxide (NO) is a gasotransmitter that binds to soluble guanylate cyclase (sGC) to produce cGMP. Impairment of this pathway has been demonstrated in neurodegenerative diseases. Normalizing deficient NO-cGMP signaling could address multiple pathophysiological features of neurodegenerative diseases. sGC stimulators are small molecules that synergize with NO, activate sGC, and increase cGMP production. Many systemic sGC stimulators have been characterized and advanced into clinical development for a variety of non-CNS pathologies. Here, we disclose the discovery of CY6463, the first brain-penetrant sGC stimulator in clinical development for the treatment of neurodegenerative diseases, and demonstrate its ability to improve neuronal activity, mediate neuroprotection, and increase cognitive performance in preclinical models. Relative to a non-CNS penetrant sGC stimulator, rodents treated with CY6463 had higher cGMP levels in CSF, fMRI-BOLD signals, and cortical electroencephalographic gamma band oscillatory power. Additionally, CY6463 improved cognitive performance in a model of cognitive disruption induced by administration of a noncompetitive NMDA receptor antagonist. In models of neurodegeneration CY6463 treatment increased LTP in hippocampal slices from a Huntington’s disease mouse model and decreased the loss of dendritic spines in aged and Alzheimer’s disease mouse models. Furthermore, CY6463 elicited an additive increase in cortical gamma band oscillatory power when co-administered with donepezil, the standard-of-care in Alzheimer’s disease. Together, these data support the clinical development of CY6463 as a novel treatment for neurodegenerative disorders.